(untitled) (Indian Journal of Animal Production and Management, 2024)
The demand for sustainably produced livestock products has been rising due to increasing consumer awareness towards animal welfare. This can be an opportunity for the migratory goat production system as they are generally believed to have enhanced welfare due to their naturalness. The present review is focused on behaviour and welfare of migratory Gaddi goats, which are primarily reared by Gaddi tribe of Himachal Pradesh. Gaddi goats spend most of daytime in feeding and walking with little time spent on standing, lying and rumination. Feeding was undertaken through grazing predominantly at high hills and through browsing in bipedal stance during lactation at low and mid-hills. Grooming activities were most evident at post-kidding and during lactation at low and mid-hills. Gaddi flocks generally have higher welfare scores, however they also faced welfare issues during their migration viz. lack good quality pasture, poor body condition, non adoption of pain management practices, parasitism (ecto and endo), abortions, lameness, rustling and wildlife attack. The welfare was found to decrease as the flock size increased. These goats showed welfare advantages in environment, behaviour, performance and health domains but disadvantage in feeding domains.